The implementation of knowledge dissemination in the prevention of occupational skin diseases. (22nd November 2017) - Wilke, A.; Bollmann, U.; Cazzaniga, S.; Hübner, A.; John, S.M.; Karadzinska‐Bislimovska, J.; Mijakoski, D.; Šimić, D.; Simon, D.; Sonsmann, F.; Stoleski, S.; Weinert, P.; et al.
Abstract: Background: Occupational skin diseases (OSD) have a high medical, social, economic and political impact. Knowledge dissemination from research activities to key stakeholders involved in health care is a prerequisite to make prevention effective. Objectives: To study and prioritize different activity fields and stakeholders that are involved in the prevention of OSD, to reflect on their inter‐relationships, to develop a strategic approach for knowledge dissemination and to develop a hands‐on tool for OSD prevention projects Methods: Seven different activity fields that are relevant in the prevention of OSD have been stepwise identified. This was followed by an impact analysis. Fifty‐five international OSD experts rated the impact and the influence of the activity fields for the prevention of OSD with a standardized questionnaire. Results: Activity fields identified to have a high impact in OSD prevention are the political system, mass media and industry. The political system has a strong but more indirect effect on the general population via the educational system, local public health services or the industry. The educational system, mass media, industry and local public health services have a strong direct impact on the OSD 'at risk' worker. Finally, a hands‐on tool for future OSD prevention projects has been developed that addresses knowledge dissemination and different stakeholder needs. Conclusion: Systematic knowledge dissemination is important to make OSD prevention more effective and to close the gap between research and practice. This study provides guidance to identify stakeholders, strategies and dissemination channels for systematic knowledge dissemination which need to be adapted to country‐specific structures, for example the social security system and healthcare systems. A key for successful knowledge dissemination is building linkages among different stakeholders, building strategic partnerships and gaining their support right from the inception phase of a project.